Efectos de la suplementación con extracto de alcachofa (Cynara scolimus L.) y cloruro de colina sobre algunas variables bioquímicas en pollos - Sandoval, G.L. (2004)
An experimental trial was carried out to verify the effects of an artichoke dry extract (Cynara scolimus L) and choline chloride supplement on some biochemical variables in broiler chickens. Three flocks of 50 birds each were divided in 2 groups (1 =treated and 2 =control). Group 1 received the supplement during the whole production cycle. At slaughter (day 50), samples of blood were collected, in order to quantify glucose, total proteins, albumin, globulin, uric acid, triglicerides, total cholesterol and the enzymes aspartate aminotransferase, lactate deshidrogenase, alkaline fosfatase and gammaglutamiltranspeptidase, being the following the average values: glucose (g/l) = 2.09 and 2.12; total proteins (g/dl) = 4.37 and 3.86; albumin (g/dl) = 1.61 and 1.59; globulins (g/dl) = 1.79 and 1.58; uric acid (mg/l) = 77.4 and 84.9; triglicerides (g/l) = 0.48 and 0.53; total cholesterol (g/l) = 1.53 and 1.43; AST (UI/l) = 270 and 234; LDH (UI/l) = 2.016 and 1.978; ALP (UI/l) = 2.366 and 2. 578; GGT (UI/l) = 26.4 and 27.4, for the groups 1 and 2, respectively. The higher concentration of plasmatic proteins in the treated group agrees with experiences carried out by other authors who attribute these effects to the action of the artichoke extract. In our investigation it should also be considered the choline chloride present in the supplement, since this nutrient contributes to preserve the metionine amino acid and to promote its endogenous synthesis. It was not possible to estimate the effect of each one component on the proteins metabolism.